ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI DALAM MENYELESAIKAN SOAL LOGARITMA DITINJAU DARI PRESTASI BELAJAR - Sherla Salsabila Adawiyah (Dharmas Education Journal (DE_Journal), 2020)
This study aims to analyze students' critical thinking skills in solving logarithmic questions in terms of learning achievement. The research subjects were students of class XI SMA Negeri 1 Mojolaban. Critical thinking skills are abilities that require students to be able to interpret, analyze, evaluate, and provide decisions or conclusions. Research is focused on critical thinking skills in solving Logarithmic problems. This study uses a qualitative approach with data collection techniques. Student achievement data were obtained from the Final Semester Assessment (PAS) document. Meanwhile, the data on students' critical thinking skills were obtained through tests. Critical thinking does not see the final result but the process carried out by students, how to interpret the questions until the decisions or conclusions are obtained. Based on the results of the study, the data obtained from the analysis of students' critical thinking skills on logarithmic material showed that 8 students were categorized as very high critical thinking skills, 10 students were categorized as high critical thinking skills, 2 students were categorized as moderate critical thinking skills, 5 students included the category of students with low critical thinking skills, and 5 students including the category of students with very low critical thinking skills.